2015
DOI: 10.1177/1532673x15597747
|View full text |Cite
|
Sign up to set email alerts
|

“You Tweet Like a Girl!”

Abstract: We investigate the Twitter activity of all congressional candidates leading up to the 2012 U.S. House elections to assess whether there are significant differences in the tone and content of the tweets from male and female candidates. We argue that the electoral environment will have a significant effect over whether candidates engage in negative tweeting, address political issues, and discuss so-called “women’s issues” on Twitter. We find that gender has both a direct and contextual effect on candidates’ comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(37 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…The lack of difference between maleand female-candidate word choice is consistent with previous research on debates (Banwart & McKinney, 2005), but not on other communication styles such as tweets (Evans & Clark, 2015). However, previous work on word use indicates that women and men use language differently, particularly their use of inclusive and exclusive words, their use of words that demonstrated tentativeness versus certainty, and their use of the pronouns I and we (e.g., Newman et al, 2008).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The lack of difference between maleand female-candidate word choice is consistent with previous research on debates (Banwart & McKinney, 2005), but not on other communication styles such as tweets (Evans & Clark, 2015). However, previous work on word use indicates that women and men use language differently, particularly their use of inclusive and exclusive words, their use of words that demonstrated tentativeness versus certainty, and their use of the pronouns I and we (e.g., Newman et al, 2008).…”
Section: Resultssupporting
confidence: 78%
“…Women and Politics, 2016). Such uneven representation has motivated scholars such as Evans and Clark (2015) to theorize that this out-group status causes "women candidates [to] adopt a different style of communication during their campaign to both combat stereotypes and to distinguish themselves from male candidates" (Evans & Clark, 2015, p. 2). Indeed, in examining tweets in 2012, they found women did tweet more attacks and more women's issues when there were fewer women in the race.…”
Section: Conservative and Liberal Brand Managementmentioning
confidence: 99%
“…The initial studies of the online self-presentation strategies employed by female and male candidates were conducted when campaign websites were commonly employed during the 2000 US election cycle (Banwart & Winfrey, 2013). The strategies utilized by female candidates diverged notably from the expected gendered stereotypes (Evans & Clark, 2015). However, no evidence demonstrated that women or men utilize gender stereotypes in Twitter microblogging or advertisements (Dolan & Lynch, 2017;Evans, 2016;Wagner et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Wagner et al (2017) found that women, as disadvantaged candidates, are more likely to use Twitter in their campaigns. Evans and Clark (2016) found that women candidates are more likely than men to attack their opponents, tweet about policy issues in general, and women's issues in particular.…”
Section: Gender and Social Mediamentioning
confidence: 99%